Sensory nerve action potential in patients with functional neurological disorders with sensory manifestations - Morimoto, Kohei; Sekiguchi, Kenji; Matsumoto, Riki (Frontiers in Neurology, 2023)
Introduction Functional neurological disorder (FND) has various clinical manifestations. Even though diagnostic criteria for FND have been proposed, FND characteristics with sensory manifestations have not been elucidated. Therefore, we aimed to investigate the association between sensory nerve action potential (SNAP) amplitudes and FND with sensory manifestations. Methods We included 76 outpatients with FND with sensory manifestations whose nerve conduction studies were performed retrospectively. Additionally, we defined 121 patients with other neurological diseases who did not have peripheral neuropathy as disease controls. The SNAP amplitudes were compared between the two groups. We also explored the relationship between SNAP amplitudes and FND-specific clinical symptoms in patients with FND. Results No differences were observed in SNAP amplitudes adjusted for age between patients with FND who had sensory manifestations and disease control patients. Additionally, no differences were observed between patients with FND who had and did not have FND-specific clinical symptoms. Conclusion The SNAP amplitude in patients with FND who had sensory manifestations was equivalent to that in controls.